Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga pada Kepuasan Konsumen (Studi Empiris pada Masyarakat Middle Income Pelanggan Gerai Ritel Jejaring Modern di Yogyakarta) - Lukas Agung Heriputranto (Universitas Katolik Soegijapranata, Semarang, 2018)
The purpose of the study is to know the influence of product quality, service quality, and price on customer satisfaction on the middle income society the customers of modern networking outlets retail in Yogyakarta. The population of this research are middle income society ascustomer of modern networking outlets retail in Yogyakarta. The sample of this research as much as 100 respondents. The sampling technique is purposive sampling. Data collection is done by questionnaire. Data analysis techniques using multiple linear regression analysis. The results showed that: (1) the product quality, service quality, and prices simultaneouslyinfluence on customer satisfaction. (2) the product quality, service quality, and price partially positive influenc on customer satisfaction.